LUKE NOTTAGE / LEON WOLFF / KENT ANDERSON (eds.), Corporate Governance in the 21st Century: Japan’s Gradual Transformation - Bälz, Moritz (Zeitschrift für Japanisches Recht, 2009)
LUKE NOTTAGE / LEON WOLFF / KENT ANDERSON (eds.), Corporate Governance in the 21st Century: Japan’s Gradual Transformation Corporations, Globalisation and the Law Series Edward Elgar Publishing, Cheltenham 2008; xii+288 pp.; £ 79.95; ISBN 978-1-84720-923-8